PENGEMBANGAN MEDIA SCRABBLE BERBASIS PICTURE AND PICTURE UNTUK KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SDN 41 LUBUKLINGGAU - Sri Ramadona, Novianti; Satinem, Yohana; Pertiwi, Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop valid, practical, and effective Pictorial and Image-Based Scrabble media to improve the reading skills of second-grade students of SD 41 Lubuk Linggau. The research method used is Research and Development (R&D) with a 4-D development model (Definition, Design, Development, and Dissemination). The subjects of this study were 28 second-grade students of SD 41 Lubuk Linggau. Data collection techniques used were observation, interviews, questionnaires, and tests. The results of the study indicate that the quality of Pictorial and Image-Based Scrabble media seen from the validity aspect is included in the